IUTAM Symposium on Multiscale Modelling of Damage and Fracture Processes in Composite Materials c - Sadowski, Tomasz; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The IUTAM Symposium on (3z(BMultiscale Modelling of Damage and Fracture Processes in Composite Materials(3y (Bwas held in Kazimierz Dolny, Poland , 23 -27 May 2005. The Symposium was attended by 48 persons from 15 countries. During 5 day meeting, 4 keynote lectures and 39 invited lectures were presented. This volume constitutes the Proceedings of the IUTAM Symposium. The main aim of the Symposium was to discuss the basic principles of damage growth and fracture processes in different types of composites: ceramic, polymer and metal matrix composites, cement and bituminous composites and wood. Nowadays, it is widely recognized that important macroscopic properties like the macroscopic stiffness and strength, are governed by processes that occur at one to several scales below the level of observation starting from nanoscale. Understanding how these processes influence the reduction of stiffness and strength is essential for the analysis of existing and the design of improved composite materials. The study of how these various length scales can be linked together or taken into account simultaneously is particular attractive for composite materials, since they have a well-defined structure at the nano, micro and meso-levels. The well-defined microstructural level can be associated with small particles or fibres, while the individual laminae can be indentified at the mesoscopic level. Moreover, the advances in multiscale modelling of damage and fracture processes to the description of the complete constitutive behaviour in composites which do not have a very well-defined microstructure, e.g. cementitious, bitumous composites and wood was analysed.s
A COMPUTATIONAL DAMAGE MICROMODEL FOR LAMINATE COMPOSITES -- NUMERICAL METHODS FOR DEBONDING IN COMPOSITE MATERIALSA Comparison of Approaches -- ATOMIC-CONTINUUM TRANSITION AT INTERFACES OF SILICON AND CARBON NANOCOMPOSITE MATERIALS -- MULTISCALE MODELLING FOR DAMAGED VISCOELASTIC PARTICULATE COMPOSITES -- A SHAKEDOWN APPROACH TO THE PROBLEM OF DAMAGE OF FIBERREINFORCED COMPOSITES -- IMPACT BEHAVIOR OF CELLULAR SOLIDS AND THEIR SANDWICH PANELS -- INFLUENCE OF DELAMINATION ON THE PREDICTION OF IMPACT DAMAGE IN COMPOSITES -- DEBONDING OR BREAKAGE OF SHORT FIBRES IN A METAL MATRIX COMPOSITE -- A MICROSCALE MODEL OF ELASTIC AND DAMAGE LONGITUDINAL SHEAR BEHAVIOR OF HIGHLY CONCENTRATED LONG FIBER COMPOSITES -- ANALYSIS OF METAL MATRIX COMPOSITES DAMAGE UNDER TRANSVERSE LOADING -- ON THE OUT-OF-PLANE INTERACTIONS BETWEEN PLY DAMAGE AND INTERFACE DAMAGE IN LAMINATES -- THE ELASTIC MODULUS AND THE THERMAL EXPANSION COEFFICIENT OF PARTICULATE COMPOSITES USING A DODECAHEDRIC MULTIVARIANT MODEL -- PREDICTION OF CRACK DEFLECTION AND KINKING IN CERAMIC LAMINATES -- COMPOSITE PLATES DYNAMIC BUCKLING OF THIN -WALLED -- NUMERICAL AND EXPERIMENTAL MODELS OF THE FRACTURE IN THE MULTI-LAYERED COMPOSITES -- MULTISCALE METHOD FOR OPTIMAL DESIGN OF COMPOSITE STRUCTURES INCORPORATING SENSORS -- NUMERICAL MULTISCALE MODELLING OF ELASTO-PLASTIC BEHAVIOR OF SUPERCONDUCTING STRAND -- ANISOTROPIC FAILURE OF THE BIOLOGICAL MULTI-COMPOSITE WOOD: A MICROMECHANICAL APPROACH -- ANTIPLANE CRACK IN A PRE-STRESSED FIBER REINFORCED ELASTIC MATERIAL -- CHARACTERIZATION AND PRACTICAL APPLICATION OF A MULTISCALE FAILURE CRITERION FOR COMPOSITE STRUCTURES -- STRESS FIELD SINGULARITIES FOR REINFORCING FIBRE WITH A SINGLE LATERAL CRACK -- NUMERICAL MODELLING OF MECHANICAL RESPONSE OF A TWO-PHASE COMPOSITE -- MODELLING OF DELAMINATION DAMAGE IN SCALED QUASI-ISOTROPIC SPECIMENS -- DAMAGE IN PATRIMONIAL MASONRY STRUCTURES -- THE MACROSCOPIC STRENGTH OF PERFORATED STEEL DISKS AT MAXIMUM ELASTIC AND LIMIT STATE -- IMPORTANCE OF SURFACE/INTERFACE EFFECT TO PROPERTIES OF MATERIALS AT NANO-SCALE -- ON A DEFORMATION OF POLYCRYSTALLINE STRUCTURES -- A MULTISCALE DAMAGE MODEL FOR COMPOSITE LAMINATE BASED ON NUMERICAL AND EXPERIMENTAL COMPLEMENTARY TESTS -- INFLUENCE OF STRENGTH HETEROGENEITY FACTOR ON CRACK SHAPE IN LAMINAR ROCK-LIKE MATERIALS -- CRACK PROPAGATION IN COMPOSITES WITH CERAMIC MATRIX -- EXPERIMENTAL INVESTIGATIONS AND MODELLING OF POROUS CERAMICS -- NUMERICAL ANALYSIS OF STRESS DISTRIBUTIONS IN ADHESIVE JOINTS.
Keywords: Engineering; Applied mathematics; Engineering mathematics; Computational intelligence; Mechanics; Mechanics, Applied; Continuum mechanics; Building materials; Materials science; Engineering; Continuum Mechanics and Mechanics of Materials; Characterization and Evaluation of Materials; Appl.Mathematics/Computational Methods of Engineering; Computational Intelligence; Theoretical and Applied Mechanics; Building Materials; Electronic books